Origin of Performance Enhancement in TiO2‐Carbon Nanotube Composite Perovskite Solar Cells. Issue 10 (10th May 2019) - Macdonald, Thomas J.; Batmunkh, Munkhbayar; Lin, Chieh‐Ting; Kim, Jinhyun; Tune, Daniel D.; Ambroz, Filip; Li, Xiaoe; Xu, Shengda; Sol, Christian; Papakonstantinou, Ioannis; McLachlan, Martyn A.; Parkin, Ivan P.; et al.
Abstract: Carbon nanotubes are shown to be beneficial additives to perovskite solar cells, and the inclusion of such nanomaterials will continue to play a crucial role in the push toward developing efficient and stable device architectures. Herein, titanium dioxide/carbon nanotube composite perovskite solar cells are fabricated, and device performance parameters are correlated with spectroscopic signatures of the materials to understand the origin of performance enhancement. By probing the charge carrier dynamics with photoluminescence and femtosecond transient absorption spectroscopy, the results indicate that charge transfer is not improved by the presence of the carbon nanotubes. Instead, carbon nanotubes are shown to passivate the electronic defect states within the titanium dioxide, which can lead to stronger radiative recombination in the titanium dioxide/carbon nanotube films. The defect passivation allows the perovskite solar cells made using an optimized titanium dioxide/carbon nanotube composite to achieve a peak power conversion efficiency of 20.4% (19% stabilized), which is one of the highest values reported for perovskite solar cells not incorporating a mixed cation light absorbing layer. The results discuss new fundamental understandings for the role of carbon nanomaterials in perovskite solar cells and present a significant step forward in advancing the field of high‐performance photovoltaics. Abstract : Device performance parameters of titanium dioxide/carbon nanotube composite perovskite solar cells are correlated with the spectroscopic signatures of the materials to determine the origin of performance enhancement. This study discusses new fundamental understandings for the role of carbon nanomaterials in perovskite solar cells and presents a significant step forward in advancing the field of high‐performance photovoltaics.